PENGARUH PROFITABILITAS, FREE CASH FLOW, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Yuliani Almalita; Partati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this research is to obtain at the factors that affect earnings management, such as profitability, leverage, institutional ownership, managerial ownership, the proportion of board commissioners, audit committee, and free cash flow. This study uses sampels from manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. This research using a purposive sampling strategy, there are 214 data and 72 companies that meet specific criteria. This study uses multiple regression was used to evaluate the hypothesis. The results of this study indicate that profitability has a positive effect on earnings management because investors ballot in companies that have a high profitable. The audit committee has a positive effect on earnings management because audit committee has integrity in monitoring financial statements, and free cash flow has a negative effect on earnings management because managements want to improve their free cash flow to show a good company’s performance to investors. Meanwhile, leverage, institutional ownership, managerial ownership, and the proportion of board commissioners have no effect on earnings management